Leveraging Data Analytics to Bridge Educational Inequities Globally - Kumari, Sangeeta; Dayal, Rajeshwar (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Introduction: It is the foundation for improving society, facilitates economic growth, achieves social equity, and incites innovation. Global educational trends indicate a vast discrepancy in literacy, enrollment, gender parity, and access to resources.Objective: Regional inequities, gaps in gender inequality, and resources are the biggest challenges facing universal quality access to education. Method: Since the research uses the Kaggle global education dataset to analyze these trends, it provides a more complete study of current challenges and achievements. Data-driven insights establish patterns, reveal disparities, and provide insight into what needs the most urgent attention. Result: The final aim is to empower the policymakers and the education stakeholders with the information necessary for creating the appropriate policies and reform practices.Conclusion: This research thus contributes to the larger goal of making the global education system more equitable and inclusive, in which everyone will have the opportunity to learn.